Effect of Leg Exercise on the Lower Limb Circulation of Patients with Diabetes Mellitus: A Systematic Review - Ida Trisnawati; I Ketut Sudiana; Supriyanto Supriyanto (Jurnal Ners, 2020)
Introduction: Hyperglycemia is one of the typical symptoms of patients with diabetes mellitus.  This systematic review aims to systematically review the research evidence related to the effects of leg exercise on increasing the value of the ankle-brachial index in patients with diabetes mellitus.Methods:  This study used a systematic review with the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) approach. We identified 85 articles from Scopus, 34 from Pubmed and 401 from ProQuest. The keywords used in the search were "Foot Exercise", "Buerger Allen Exercise" and "Diabetes Mellitus". The inclusion criteria for this study were 1) Interventions with a focus on the Buerger Allen Exercise and 2) papers published in English. The deadline for publication was between 2014 and 2019.Results: After going through the selection process, 8 articles were deemed to be relevant for inclusion in this systematic review. One effort to overcome the interference of lower limb circulation is through physical exercise in the form of leg exercises. The exercises that can be applied are Buerger Allen Exercises.Conclussion: The simplest examination that can be done to detect any interference with lower limb circulation is to measure the value of the Ankle Brachial Index (ABI)